Qualitative analysis of a community pharmacy practice transformation initiative. Issue 12 (20th November 2022) - Bacci, Jennifer L.; Ferreri, Stefanie P.; Coley, Kim C.; Daly, Christopher J.; Hake, Kelsey L.; Herbert, Sophia M. C.; Hughes, Tamera D.; McDonough, Randal P.; Roller, Jessica S.; McGivney, Melissa Somma; Smith, Megan; Doucette, William R.
Abstract: Objective: To evaluate practice transformation team (PTT) members' perceptions of the Flip the Pharmacy (FtP) initiative as a strategy for implementing and improving community pharmacy‐based patient care. Methods: FtP is a national 2‐year practice transformation initiative for implementing enhanced patient care and medication optimization services at community pharmacies, launched in 2019 with 28 PTTs including over 500 pharmacy locations. Key informant interviews were conducted with team leads, coaches, and pharmacy champions from four PTTs that participated in the first FtP cohort. The interviews were conducted using semistructured interview guides based on the RE‐AIM framework and focused on participants' experiences in the first year of FtP. Interviews were audio‐recorded, transcribed, and analyzed using a rapid content analysis approach. Results: Four leads, 8 coaches, and 8 pharmacy champions were interviewed from 4 PTTs from May to October 2021 and resulted in 10 themes: (1) community pharmacy practice experience is important when selecting coaches; (2) team readiness supports successful pharmacy practice transformation; (3) measures of patient care quality are needed; (4) payment and practice transformation opportunities happen in parallel; (5) successful practice transformation requires strategic involvement of the entire pharmacy team; (6) FtP practice transformation domains are synergistic; (7) change packages, coaching, and performance monitoring are core practice transformation supports; (8) pharmacy teams value opportunities to share and learn from each other; (9) sustaining patient care services is continuous; and (10) COVID‐19 accelerated practice transformation while creating new stress points. Conclusion: Participants in this study perceived the FtP initiative as a helpful strategy implementing and improving community pharmacy‐based patient care. Future research should explore the sustainability of the FtP initiative and similar community pharmacy practice transformation efforts.